The Use of Legal Psychology in Determining Sexual Misconduct Perpetrator’s Bad Intention Towards Children - Novritsar Hasintongan Pakpahan; Binsar Pamopo Pakpahan (Penerbit Goodwood, 2024)
Purpose: The aim of the study is to discover bad intention (mens rea) of sexual misconduct perpetrator by using legal psychology in finding legal obscurity of trial-proving within child protection act Methodology/approach: The research is conducted as legal research, namely normative research that applies the statute approach and conceptual approach towards the object of the study based on primary and secondary sources of law. Results/findings: Discovering and solving legal obscurity in bad intention within sexual harassment regulation, then legal psychology can be utilized by law enforcement to prove and decide criminal act of a subject by analyzing its criminal mindset while recognizing its culpability mental state Limitations: the use of legal psychology only relating to criminal law field of study Contribution: This study contributes to legal practitioners, especially prosecutors and judges, especially in criminal law.